Understanding the stability of an unprecedented Si-Be bond within quantum confinement - Maneri, Asma Harun; Krishnamurty, Sailaja; Joshi, Krati (ACS Omega, 2023)
As of today, the Si-Be bond remains underexplored in the literature, and therefore its anomalous behavior continues to be an unsolved puzzle to date. Therefore, the present study aims at evaluating the integrity of an unprecedented Si-Be bond within quantum confinement. To accomplish this, first-principles-based calculation are performed on Be-doped silicon clusters with atomic sizes 6, 7, and 10. Silicon clusters are sequentially doped with one, two, and three Be atoms, and their thermal response is registered in the temperature range of 200-1500 K, which discloses several research findings. During the course of the simulations, the clusters face various thermal events such as solid cluster phase, rapid structural metamorphosis, and fragmentation. Si-Be nanoalloy clusters are noted to be thermally stable at lower temperatures (200-700 K); however, they begins to disintegrate earlier at a temperature as low as 800 K. This lower stability is attributed to the weak nature of Si and Be heteroatomic interactions, which is corroborated from the structural and electronic property analysis of the doped clusters. In addition to this, the performance of Be-doped clusters at finite temperatures is also compared with the thermal response of two other popular systems, viz., C-and B-doped silicon clusters.